2023
DOI: 10.22198/rys2023/35/1717
|View full text |Cite
|
Sign up to set email alerts
|

Autoabasto en la dieta campesina del Totonacapan poblano (México): implicaciones para la agrodiversidad

Abstract: Objetivo: caracterizar el patrón alimentario de las familias campesinas y determinar la influencia de los factores socioeconómicos en el origen y consumo de los alimentos en el Totonacapan poblano (México). Metodología: con la técnica de recordatorio de 24 horas, se aplicó una encuesta a 270 familias sobre su dieta y se documentó la información socioeconómica. Resultados: se registraron 159 alimentos, de los cuales 57.6% tiene procedencia externa e incluyen grasas, lácteos, huevo, pan, pasta de trigo, sal y al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…For the analysis, the vegetable group did not include chili, tomato, and squash. n: 69. other varieties of chilies and beans, considered staples in the peasant diet, showed a high consumption frequency in contrast to their low presence in the farm plots, which could be related to the fact that local and regional markets are selling foods from outside the region that are replacing those grown on the plots (Espinoza-Pérez et al, 2023). It is not clear whether the decrease in local production is because products can be bought in the markets or whether families buy in the market due to the decrease in local production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the analysis, the vegetable group did not include chili, tomato, and squash. n: 69. other varieties of chilies and beans, considered staples in the peasant diet, showed a high consumption frequency in contrast to their low presence in the farm plots, which could be related to the fact that local and regional markets are selling foods from outside the region that are replacing those grown on the plots (Espinoza-Pérez et al, 2023). It is not clear whether the decrease in local production is because products can be bought in the markets or whether families buy in the market due to the decrease in local production.…”
Section: Discussionmentioning
confidence: 99%
“…According to the statistical tests performed in the previous study, factors such as income and environment did not influence food availability. From the previously mentioned research, four dietary profiles were identified and grouped according to the frequency of consumption and the origin of the food (A, B, C, and D) (Espinoza-Pérez et al, 2023). Households in groups A and D consumed more frequently self-produced and locally produced foods (corn, beans, chili pepper, local vegetables) were named regional food groups.…”
Section: Study Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Aunque las personas de comunidades totonacas pueden consumir alimentos industrializados, ellos también incorporan en su dieta una variedad de alimentos que incluyen productos vegetales como tubérculos, raíces, cereales, frutos, verduras, quelites, hierbas, leguminosas, miel silvestre, carne de animales de traspatio (por ejemplo, aves, cerdo) y silvestres (por ejemplo, armadillo) y derivados de animales como huevos y manteca. Se ha registrado que los totonacas pueden consumir o identificar entre 35 y 160 ítems comestibles de los cuales los productos de la milpa, como el maíz, el chile de árbol, la calabaza y el frijol son los más consumidos (Espinoza-Pérez et al, 2023;García-Vázquez et al, 2022). Además, los platillos de la región son gastronómicamente enriquecidos con hierbas, semillas u otros ítems alimentarios que, aunque pueden pasar desapercibidos en el platillo, enriquecen la dieta con macro y micronutrientes.…”
Section: Las Dietas Tradicionales Su Impacto En El Microbioma Intesti...unclassified